Blockchain Application Guide Methodology and Practice - Tang, Xiaodan; Deng, Xiaotie; Bie, Rongfang (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book focuses on progress, concerns and approaches of blockchain application. It summarizes basic concepts, principles and standardization of blockchain technology, as well as the status of blockchain application and industry. It provides an ecology model and an evaluation method for blockchain applications and analyses the governance of blockchain applications. It presents application values and practices in financial services, logistics, government service, culture and education, and people's livelihood and includes analysis of scenarios and use cases. This book is a summary of the experience of more than 20 experts from enterprises and institutions active in the blockchain industry. It provides a panorama of blockchain applications for users, technology and service providers, application developers and operators and supervisors.
Overview of Blockchain -- The Fusion of Blockchain and the New-Generation Information Technology -- Blockchain Application Status and Ecology -- Implementation Route of Blockchain Application -- Blockchain and Financial Services -- Blockchain and Logistics -- Blockchain and Government Services -- Blockchain and Culture and Education -- Blockchain and People's Livelihood -- Blockchain Application Governance -- Blockchain Application Evaluation Method -- Blockchain Standardization Route -- Key Issues of Blockchain -- Trend Analysis of Blockchain.
Keywords: Computational intelligence; Artificial intelligence; Industrial engineering; Production engineering; Computational Intelligence; Artificial Intelligence; Industrial and Production Engineering